Inhibition of Notch signaling affects hepatic oval cell response in rat model of 2AAF-PH - Darwiche H (Dove Medical Press, 2011)
Houda Darwiche, Seh-Hoon Oh, Nicole C Steiger-Luther, Jennifer M Williams, Dana G Pintilie, Thomas D Shupe, Bryon E PetersenDepartment of Pathology, Immunology, and Laboratory Medicine, Program in Stem Cell Biology and Regenerative Medicine, College of Medicine, University of Florida, Gainesville, FL, USABackground and aims: Activation of the oval cell compartment occurs in the liver when hepatocytes are functionally compromised and/or unable to divide. Our goal was to investigate the systemic signals responsible for determining the efficiency of oval cell-mediated liver regeneration, focusing on the Notch signaling cascade.Methods: The established oval cell induction protocol of 2-acetylaminofluorine (2-AAF) implantation followed by 70% surgical resection of the liver (partial hepatectomy, PH) was employed in a rat model. This oval cell induction model was further combined with injections of a γ-secretase inhibitor (GSI XX) to examine the effects of Notch inhibition on oval cell-aided regeneration of the liver.Results: Notch signaling was found to be upregulated at the peak of oval cell induction during 2AAF-PH alone. Treatment with GSI XX led to interruption of the Notch signal, as shown by a decrease in expression of Hes1. While there was a robust oval cell response seen at day 11 post-PH, there was a measurable delay in differentiation when Notch was inhibited. This was confirmed morphologically as well as by immunohistochemistry for the oval cell markers, α-fetoprotein, OV-6, and CK19. The hepatocytes seen at day 22 demonstrated an enhanced hepatocellular mitoinhibition index (p21Waf1/Ki67), suggestive of dysregulated proliferation and cell cycle progression. Moreover, these hepatocytes exhibited decreased expression of hepatocyte functional markers, such as cytochrome P450 and glucose-6-phosphatase-α.Conclusion: Taken together, these results identify the Notch signaling pathway as a potent regulator of differentiation and proliferation in oval cells, which is necessary for functional repair of the liver by oval cells.Keywords: Notch, oval cells, liver, regeneration, differentiation